2019
DOI: 10.1590/0100-29452019028
|View full text |Cite
|
Sign up to set email alerts
|

Quality and functional properties of ‘Tupy’ blackberry stored in modified atmosphere conditions

Abstract: The aim of this work was to evaluate the effect of storage temperature, in passive modified atmosphere (MA) and atmospheric composition in active MA on quality maintenance, total phenolic compounds (TPC) and total antioxidant activity (TAA; DPPH and ABTS methods) of 'Tupy' blackberry. Two experiments were carried out. In experiment 1, the fruit were stored for eight days at 0, 5 and 10 °C in passive MA. In experiment 2, the initial atmospheres of 21.0 kPa O 2 + 0.04 kPa CO 2 (passive MA); 9.2 kPa O 2 + 9.2 kPa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…In addition to organic acids, including citric acids, which are also converted into sugars as maturation progresses (Moreno & Oyla, 2016) and together lead to an increase in the soluble solids content of fruits. It is worth noting that the fruits harvested in RS3 had an average SS content of 11.54 °Brix, which is higher than that found by Soethe et al (2019), who at the end of 8 days of storage in modified atmosphere, found an SS content of 8.5 ° Brix for the Tupy cultivar, wich is currently the most cultivated in Brazil. This shows the great marketing potential of the BRS Cainguá cultivar for in natura consumption, due to the high SS content of its fruits.…”
Section: Resultscontrasting
confidence: 55%
See 1 more Smart Citation
“…In addition to organic acids, including citric acids, which are also converted into sugars as maturation progresses (Moreno & Oyla, 2016) and together lead to an increase in the soluble solids content of fruits. It is worth noting that the fruits harvested in RS3 had an average SS content of 11.54 °Brix, which is higher than that found by Soethe et al (2019), who at the end of 8 days of storage in modified atmosphere, found an SS content of 8.5 ° Brix for the Tupy cultivar, wich is currently the most cultivated in Brazil. This shows the great marketing potential of the BRS Cainguá cultivar for in natura consumption, due to the high SS content of its fruits.…”
Section: Resultscontrasting
confidence: 55%
“…During refrigerated storage, the SS/TA ratio of RS3 and RS2 fruits show an increasing linear adjustment at the end of 12 days of storage, reaching values of 15.13 and 8.64, respectively, (Table 2). This increase in SS/TA is due to the reduction in TA during fruit storage, as organic acids are used as substrates in respiratory metabolism (Soethe et al, 2019) and the SS content did not change during storage as seen in table 1. Although fruits harvested in RS2 showed changes in the SS/TA ratio during storage, in no period was the SS/TA ratio equal to or greater than that presented by RS3 fruits on the day of harvest, or even after 12 days of storage.…”
Section: Resultsmentioning
confidence: 90%
“…Conversely, Soethe et al. (2019) have shown CA to exhibit no significant difference in the biochemical quality of “Tupy” blackberry fruit over control fruit. Oxygen saturated (>80%) CA storage, which maintains higher TPC, AsA, and antioxidant levels, presented better fruit quality in terms of biochemical and quality attributes of “Black Satin” blackberry fruit (Van de Velde et al., 2020).…”
Section: Postharvest Quality Management Of Rubus Berriesmentioning
confidence: 96%